What's the price of consulting? Effects of public and private sector consulting on academic research - Roman Fudickar; Hanna Hottenrott; Cornelia Lawson (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2016)
Academic consulting is recognised as an important and effective means of knowledge transfer with the public and private sectors. These interactions with external sectors offer opportunities for research application but also raise concerns over their potentially negative consequences for academic research and its dissemination. For a sample of social, natural and engineering science academics in Germany, we find consulting to be widespread, undertaken by academics at all seniority levels and in all disciplines, with academics in the social sciences more likely to provide advice to the public sector and those in engineering to the private sector. Controlling for the selection into consulting, we then investigate its effect on research performance. While previous research suggested that consulting activities might come at the cost of reduced research output, our analysis does not confirm this concern. The results, however, suggest that stronger engagement in consulting increases the probability to cease publishing research altogether. Moreover, public sector consulting comes with lower average citations which may suggest a move towards context-specific publications that attract fewer citations. We draw lessons for research institutions and policy about the promotion of academic consulting.
Keywords: O31; O33; O38; I23; 330; academic consulting; university-industry interaction; science advice; knowledge transfer; research performance; exit from academia